Side Effects of COVID-19 Inactivated Virus vs. Adenoviral Vector Vaccines: Experience of Algerian Healthcare Workers - Lounis, Mohamed; Rais, Mohammed Amir; Bencherit, Djihad; Aouissi, Hani Amir; Oudjedi, Adda; Klugarová, Jitka; Pokorná, Andrea; Klugar, Miloslav; Riad, Abanoub (Frontiers in Public Health, 2022)
Healthcare workers have been were prioritized in vaccination campaigns in almost all countries because they are exposed to the highest risk of contamination by SARS-CoV-2. This study was conducted to evaluate the self-reported post-vaccination side effects of inactivated (Sinopharm and CoronaVac) and adenoviral vector-based (AstraZeneca-Oxford, Sputnik V and Janssen) vaccines among Algerian healthcare workers using a validated questionnaire. The final analysis included a total of 721 healthcare workers, with a predominance of females (59.1%) and younger individuals of 20–30 years-old (39.4%). Less than half (49.1%) of the respondents reported at least one local side effect, while 53.8% reported at least one systemic side effect. These side effects were more prevalent among viral vector vaccinees than inactivated virus vaccinees. The most common local side effects were injection site pain (39%) and arm pain (25.4%), while fatigue (34.4%), fever (28.4%), headache (24.8%) and myalgia (22.7%) were the most prevalent systemic side effects. The side effects appeared earlier among inactivated virus vaccines recipients and generally lasted for two to three days for the two vaccinated groups. The risk factors associated with a higher prevalence of side effects included female gender, allergic individuals, individuals with regular medication, those who contracted the COVID-19 disease and those who received two doses for both inactivated and viral-based vaccines groups. Despite the higher prevalence of post-vaccination side effects among adenoviral vector vaccines recipients, both vaccines groups were equally effective in preventing symptomatic infections, and no life-threatening side effects were reported in either vaccine group.